Legal Position of Environmental Management as an Instrument for Preventing Environmental Damage and Pollution - Indra Gunawan Purba; Muhammad Siddiq; Ori Atmaja Sinulingga; Salfister Thomas Barus; Andria Maulana Prabowo; Muhammad Yogi Syahputra (International Journal of Science and Environment (IJSE), 2025)
This research aims to investigate the impact of workload and work environment on employee turnover intention at PT. XYZ. High turnover intentions can disrupt workforce stability and result in significant costs for the company. Two factors often associated with turnover intention are workload and work environment. Excessive workload can cause stress and fatigue, while an unsupportive work environment can reduce employee satisfaction and commitment. The study uses a quantitative approach, distributing questionnaires to 107 employees and sampling using the saturated sample method. Data analysis was conducted using SEM-PLS software. The hypothesis test tested the influence of workload and work environment on employee turnover intention. The results showed that workload variable (X1) is in the high category, work environment variable (X2) is in the bad category, and turnover intention (Y) is in the medium category. Quantitative data analysis with SEM-PLS showed that workload variables do not have a significant influence on turnover intention, while work environment variables have a significant influence. The research aims to evaluate company management's attention to workload and work environment conditions, with one variable showing a significant positive influence on employee turnover intention.